2013
DOI: 10.1136/emermed-2013-202772
|View full text |Cite
|
Sign up to set email alerts
|

THERM: the Resuscitation Management score. A prognostic tool to identify critically ill patients in the emergency department

Abstract: PEDS is at least as good as other scores, including NEWS. However, it is unwieldy and relies on results not immediately accessible in the ED. THERM is a new score, derived and validated in an ED setting, using variables readily available, and simple to calculate and stratify. THERM outperforms NEWS and could be used in preference in critically ill ED patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…81 The same findings have been reported for the REMS (Rapid Emergency Medicine Score), 82 MEDS (modified mortality in emergency department sepsis) 83 and THERM (The Resuscitation Management Score) 84 scores in the ED, the PREEMPT-2 (PRE-critical Emergency Medical Patient Triage) and PREAMBLE-2 (PRE-Admission Medical Blue-Light Emergency) scores in acute medical admissions 85 and CREWS (Chronic Respiratory Early Warning Score) for respiratory disease. 86 Care must be taken when using early warning scores in certain subspecialties.…”
Section: Limitations Of Early Warning Scoressupporting
confidence: 70%
“…81 The same findings have been reported for the REMS (Rapid Emergency Medicine Score), 82 MEDS (modified mortality in emergency department sepsis) 83 and THERM (The Resuscitation Management Score) 84 scores in the ED, the PREEMPT-2 (PRE-critical Emergency Medical Patient Triage) and PREAMBLE-2 (PRE-Admission Medical Blue-Light Emergency) scores in acute medical admissions 85 and CREWS (Chronic Respiratory Early Warning Score) for respiratory disease. 86 Care must be taken when using early warning scores in certain subspecialties.…”
Section: Limitations Of Early Warning Scoressupporting
confidence: 70%
“…Several studies have reported that REMS was superior to MEWS (2011 to 2019 in Israel, Taiwan, China, and Turkey) [ 20 , 23 , 24 , 31 ], which is in contrast to the results of the current study and other evidence presented in Table 5 [ 3 , 22 , 27 ]. Consistent with our findings, researches from the United States and Turkey indicate that the performance of these two models is similar to each other [ 2 , 3 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors have argued that disease‐specific or condition‐specific EWSs might be required when EWS systems are used outside the patient population in which they were developed. The findings of the present study suggest that, for admissions to surgical specialties, a change in trigger level could be all that is required as a NEWS value of 4 for non‐elective admissions to surgical specialties has equivalent efficiency to a NEWS value of 5 for medicine.…”
Section: Discussionmentioning
confidence: 99%